(untitled) (Fiep Bulletin - online, 2014)
To analyze patients permanence time in clinical treatment as well as the assistance complexity level in a specific healthcare center. Methodology: descriptive, retrospective and documentary study with quantitative approach. The data was collected from an electronic record from patients in a Public Teaching Hospital. To analyze the assistance complexity level we used the Patient Classification System according to Fugulin. Results: 244 patients were evaluated; 38,9% were over 60 years old and presented a wider permanence time when compared to other age groups; 45,3% were classified as chronical patients with full nursing assistance dependence. Conclusion: The SCP usage provides us with information regarding the patients in order to improve the given assistance for them and their families.